Virtual laboratory simulation in the education of laboratory technicians–motivation and study intensity. Issue 3 (12th February 2019) - de Vries, Lisbeth Elvira; May, Michael
Abstract: This study presents an evaluation of virtual laboratory simulation for educational use in the AP Degree Programme in Chemical and Biotechnical Science at University College Copenhagen in Denmark. The purpose was to test if, and how, virtual laboratory simulation could be applied to a practically oriented education such as the education of laboratory technicians—the aim being to motivate students and improve the education with new teaching tools. The study investigated how specific virtual lab simulation cases (Labster‐cases) may stimulate motivation, study intensity, and learning among laboratory technician students. Altogether, 78 students evaluated different educational aspects of using virtual lab cases in relation to a 2‐week course within gene technology. Overall, students were positive regarding the use of laboratory simulation as well as the specific cases tested. The study showed that virtual lab simulation seems to help laboratory technician students connect theory with practice and to visualize molecular processes as well as practical laboratory procedures and instrument techniques, however, it did also pose technical challenges. Furthermore, the study indicated that the use of virtual lab simulation cases can contribute to increased study activity as well as motivation. The overall conclusion of this study was that virtual lab simulation is an effective supplement to traditional teaching activities for the education of lab technicians. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):257–262, 2019.